In Situ Observations and Tuning of Physical and Chemical Phenomena on the Surfaces of Strongly Correlated Oxides. (5th April 2013) - Gai, Zheng; Kalinin, S. V.; Li, An‐Ping; Shen, Jian; Baddorf, A. P.
Abstract The characteristic aspect of strongly correlated oxides systems is the strong coupling between the structural, electronic and magnetic properties. A small change in one property can produce a large change in another. Controllable surface tuning provides the opportunity to study how structural, electronic, and magnetic properties respond to the broken symmetry and opens avenues for exploration of completely new physical properties. The extreme sensitivity of properties to external chemical and physical stimuli makes in situ characterization a requirement for controlled tuning of complex correlated materials. This paper reviews some recent progress in in situ observations and tuning of physical and chemical phenomena on the surfaces of strongly correlated oxides thin films and crystals, including atomic‐level structural studies, control, and tuning of the physical properties.